Characteristics of boulders formed in tropical weathered granite: a review - Md Dana, Mohd. Firdaus (Penerbit UTM Press, 2016)
Boulder is well known as one of the obstruction material and problematic to the underground excavations and constructions. Although the presence of boulder in weathered rock mass was revealed and reported by many researchers, but the occurrence and physical characteristics of boulders in weathering profile are still not clearly understood. This paper attempts to revise the issues and characteristics of boulder formed in weathered granite which include the formation, distribution, properties and location of boulders found in tropical weathering profile. As a weathering product, boulder is dominantly found in moderately to completely weathered zone of rock mass (Grade III to V). Boulder consists of corestone Grade I or II and surrounded by some concentric sheet of weathered rock Grade III to V or rindlets which formed due the reaction of spheroidal weathering. The rindlets with thickness ranges 0.2 mm to 2.0 m is the zone of decomposition and dissolution of biotite and feldspar that gradually transforming to saprolite. This information is useful to geotechnical engineers and researchers for engineering purposes and weathering zone classification especially in underground excavation and structure design.